Trend analysis in reference evapotranspiration using Mann-Kendall and Spearman’s Rho tests in semi arid region of North Gujarat - MAKWANA, JAYDIP J.; DEORA, B. S.; PARMAR, B. S.; PATEL, C. K. (Journal of Soil and Water Conservation, 2020)
Evapotranspiration (ET) is an important element of the hydrological cycle, and changes in ET holds a great significance to agricultural water-use planning, irrigation system design and management. In this study, monthly trends of reference evapotranspiration (ET0) were examined using Mann-Kendall (MK) test, Spearman’s Rho test (SR) and the Sen’s slope estimator for Sardarkrushinagar, Gujarat, India. For this purpose, meteorological observations were collected over a period of 29 years (1988–2016). The results indicated that trends of ET0 for some months were increasing (positive) however, for some months, there were decreasing (negative) trends. The significant and highly significant ET0 trends on a monthly time scale occurred during the months of January, February, March, August, October and December, but no significant trend were observed for April, May, June, July, September and November months. The highest positive ET0 trend (0.81 mm/month) and decreasing ET0 trend (0.45 mm/month) were found during March and September, respectively. In general, the performances and abilities of the MK, SR and Sen’s slope estimator were consistent at the verified significant level.